A Mixed-Method Approach to Develop and Validate an Integrated Food Literacy Tool for Personalized Food Literacy Guidance - Boedt, Tessy; Steenackers, Nele; Verbeke, Joke; Vermeulen, Astrid; De Backer, Charlotte; Yiga, Peter; Matthys, Christophe (Frontiers in Nutrition, 2022)
Background: Food literacy refers to all practicalities associated with healthy eating. Current food literacy tools are limited in practical use in clinical practice. Therefore, an integrated food literacy tool (IFLT) to assess food literacy and to personalize food literacy guidance was developed and validated. Methods: Following an iterative process, a food literacy framework was developed and food literacy goals were defined. A corresponding food literacy screener (FLS) to assess food literacy was developed along with an algorithm to provide personalized food literacy guidance based on the food literacy assessment. Content validation of the FLS was assessed by a panel of experts, measuring item and scale content validity index (I/S-CVI) and by the target population in semi structured interviews with 15 adults of reproductive age. Subsequently, an online cross-sectional survey was conducted among 114 adults of reproductive age to evaluate the validity of the FLS. Construct validity was examined against both the validated healthy eating and weight self-efficacy scale and against a food frequency questionnaire assessing healthy eating self-efficacy (HESE) and diet quality, respectively. Reliability was assessed with a two-week test-retest. Pearson correlation tests were conducted. Results: An IFLT consisting of a FLS and corresponding algorithm to personalize food literacy guidance by prioritizing food literacy goals was developed. The IFLT includes 24 food literacy goals, addressed by 17 FLS items. Every item received a weighting factor based on theory and expert opinion to prioritize food literacy goals according to personal needs. Content validity revealed that the FLS was rated relevant by experts (S-CVI = 0.93) and well understood by the target population. The FLS has a good construct validity as it was positively correlated with diet quality (r=0.536, p<0.001) and with HESE (r=0.685, p<0.001). It also showed a good test-retest reliability (r=0.721, p<0.001). Conclusions: The newly developed IFLT is a practically applicable, context specific theory-and expert-based dual purpose tool to assess food literacy and to personalize food literacy guidance by prioritizing individuals’ food literacy goals to their needs.